PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUGMENTED REALITY BAGI SISWA SEKOLAH DASAR DI SUMATERA BARAT DENGAN PENDEKATAN JOYFUL LEARNING: A SYSTEMATIC LITERATURE REVIEW - M. Yakub Iskandar; Efendi Efendi; Ramadhani Ramadhani; Sefrinal Sefrinal; Okviani Syafti; Taufik Abdul Hasan Amarullah; Dino Adi Putra (Jurnal Manajemen Pendidikan, 2025)
The use of Augmented Reality (AR) technology in elementary education is growing in line with the demands of 21st-century learning that emphasizes interactive, contextual, and meaningful learning experiences. This study aims to systematically analyze the effect of the use of Augmented Reality-based learning media on the learning process and outcomes of elementary school students in West Sumatra Province using the Joyful Learning approach. The method used is a Systematic Literature Review (SLR) of accredited national journal articles published in the last ten years and relevant to the topics of AR, Joyful Learning, and elementary school education. The results of the study indicate that the use of AR learning media consistently has a positive impact on increasing learning motivation, conceptual understanding, active student involvement, and positive attitudes towards learning, especially when combined with the Joyful Learning approach. In addition, AR can help elementary school students understand abstract concepts through interactive and contextual three-dimensional visualizations. However, several studies also highlight implementation challenges, such as limitations in technological infrastructure and teacher readiness in integrating AR pedagogically.